LONG DISTANCE MARRIAGE; Fulfillment of Biological Rights and Marital Harmony in the City of Pekanbaru - Mustafa, Ali; Pratama, Herdifa (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
The phenomenon and study of long distance marriage couples is a very interesting thing to research. This research seeks to determine the implementation of fulfilling the biological rights of long distance marriage couples and how to maintain household harmony even though they are far apart in Pekanbaru City. The method used in this research is qualitative research through phenomenological studies explained observationally. This research was designed in the form of field research, namely research carried out by going directly to the field and interviewing 15 couples. Through this research, it was found that the respondents who underwent long distance marriages each responded differently to this biological problem because the frequency of their encounters was different. There are once every week, every four months and six months. There are those who are used to it and there are those who still really have a problem with it. Biological desires that are not channeled will have an impact on a person's physical and emotional state which will ultimately also affect household relationships. So the things that respondents did when the desire arose included taking a walk, eating, keeping their gaze, holding back as much as possible, and making a masturbation video call. This kind of long distance marriage condition requires each partner to commit to remaining together even though they are separated by distance and time and to consult if there is a commotion between the husband and wife